Perlindungan Hukum bagi Jurnalis dalam Peliputan Demonstrasi - Joko Susanto; Sasetya Bayu Effendi; Rinanda Asrian Ilmanta; Royce Wijaya Setya Putra; Reza Aulya Ramadhan (Institut Teknologi dan Bisnis Semarang, 2024)
This journal discusses the legal protections that journalists receive in covering demonstrations. The study aims to identify the legal challenges faced by journalists during the coverage of demonstrations and to propose solutions that can improve legal protection for journalists. The research methodology used in this study is a qualitative approach with data collection techniques through in-depth interviews with journalists who have covered demonstrations. The results showed that journalists faced various risks and legal challenges during their coverage of demonstrations, including physical violence, intimidation, and interference in carrying out their journalistic duties. However, by applying a social systems theory approach, this study proposes that collaboration between authorities, journalists, media offices and civil society organizations can strengthen legal protections for journalists in demonstration situations. Thus, this collaborative effort is expected to create a safer and more supportive environment for journalists in carrying out their journalistic duties during the coverage of demonstrations.